Comparison of Adrenergic Beta-receptor Antagonists in Angina Pectoris. Issue 5846 (20th January 1973) - Thadani, U.; Sharma, B.; Meeran, M. K.; Majid, P. A.; Whitaker, W.; Taylor, S. H.
Abstract : The symptomatic, electrocardiographic, and circulatory effects of intravenous and oral preparations of propranolol, oxprenolol, and practolol were compared in 16 patients with uncomplicated angina pectoris precipitated by exertion. The method of study included treadmill exercise, double-blind assessment, single-blind analysis, with placebo control and randomized serial comparison of each drug in each patient. The doses used were selected to give the same near-maximum suppression of the heart rate response to exercise. The symptomatic, electrocardiographic, and circulatory response of each patient to both preparations of each of the three drugs was similar. Exercise tolerance was increased in two-thirds, unchanged in one-sixth, and significantly worsened in one-sixth of the studies. Electrocardiographic evidence of myocardial ischaemia was conspicuously reduced by all three drugs in most studies irrespective of their symptomatic effects. Though the exclusive choice of patients, the single dose design of the trial, and the treadmill method of assessment limit the general application of these results, they do clearly indicate that in doses that induce equal suppression of the exercise heart rate these three drugs have similar distinct anti-anginal activity. Their ancillary pharmacological properties are probably of little importance in this respect. Equally, the similarity in the symptomatic, circulatory, and electrocardiographic response to the intravenous and oral preparations suggests that metabolic breakdown products are probably of therapeutic importance only in so far as they antagonize beta-receptor activity.